2013
DOI: 10.1103/physreva.88.012717
|View full text |Cite
|
Sign up to set email alerts
|

Positron scattering from pyrimidine

Abstract: In the present work we report on our experimental total cross section and positronium formation cross-section results for positron scattering from pyrimidine for energies from 1 to 180 eV. In addition, the total inelastic integral cross sections (for electronic excitations plus direct ionization) have been measured up to 21.5 eV. We also report quasi-elastic total and differential cross sections at energies up to 21.5 eV. Our results are compared to recent theoretical and experimental data for positron scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(76 citation statements)
references
References 22 publications
13
62
1
Order By: Relevance
“…Specifically, the IAM SCAR results are a factor of 3.4-4.4 larger in magnitude than the corrected experimental data at the common impact energies. This is somewhat surprising, given the quite fair accord we have found between the IAM SCAR calculations and cross sections measured at Trento or the Australian Positron Beamline Facility [26,59,73] for some other large polyatomic molecules. We note, however, that for yet further targets the level of accord was not so good or not uniformly good at all energies [55,58,72].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Specifically, the IAM SCAR results are a factor of 3.4-4.4 larger in magnitude than the corrected experimental data at the common impact energies. This is somewhat surprising, given the quite fair accord we have found between the IAM SCAR calculations and cross sections measured at Trento or the Australian Positron Beamline Facility [26,59,73] for some other large polyatomic molecules. We note, however, that for yet further targets the level of accord was not so good or not uniformly good at all energies [55,58,72].…”
Section: Resultsmentioning
confidence: 69%
“…However, the situation with respect to positron scattering is somewhat poorer, with only a limited number of measurements [20,[25][26][27] and calculations [27][28][29][30] being available. In particular, we note that both the experimental and theoretical effort was largely dedicated to the investigation of the pyrimidine bases, such as pyrimidine itself [20,26,30] and uracil [25,27]. Indeed, there is only one computation for positron impact with the purine bases [29], namely, adenine and guanine, and no measurements to validate that calculation.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive study on the VUV electronic state spectroscopy of pyrimidine has been reported by Ferreira da Silva et al [20] in the energy range 3.7-10.8 eV together with a comprehensive electron energy loss spectroscopy (EELS) of the singlet excitations in the range 2-15 eV. However, experimental total scattering CSs have, to the best of our knowledge, only been obtained for positrons as a projectile [10,21]. This is something of an oversight by the scattering community, because the total CS, being the sum of the integral cross sections for all possible scattering processes, represents a vital self-consistency check for those integral cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows a comparison of the elastic DCSs for the three pentane isomers, calculated using the IAM-SCAR approach, at six selected impact energies between 1 and 50 eV. All the DCSs show a forward-peaked shape which is typical of polar molecules (see, e.g., Tattersall et al, 2014;Chiari et al, 2013aChiari et al, , 2013dand Palihawadana et al, 2013) and become more isotropic as the incident positron energy is decreased. Note that the DCSs for isopentane are averaged over the rotational excitations, whereas those for the other two isomers are not given that they are non-polar.…”
Section: Comparison Of the Three Isomers: Isomer Effectmentioning
confidence: 99%